2018
DOI: 10.1111/ene.13677
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, edema and poor outcome are associated with hyperthermia in hypertensive intracerebral hemorrhages

Abstract: Background and purposeThe deleterious effect of hyperthermia on intracerebral hemorrhage (ICH) has been studied. However, the results are not conclusive and new studies are needed to elucidate clinical factors that influence the poor outcome. The aim of this study was to identify the clinical factors (including ICH etiology) that influence the poor outcome associated with hyperthermia and ICH. We also tried to identify potential mechanisms involved in hyperthermia during ICH.MethodsWe conducted a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…This is probably due to the multiple mechanisms that can condition the temperature increase in ICH, and the type of hemorrhage is undoubtedly one of these variables. 13 In our series, the therapeutic response was positive in only 31.1% of hypertensive ICH, in 42.9% of amyloid ICH, in 25.0% associated with antiplatelets/anticoagulants, and in 74.2% of indeterminate cases (p < 0.0001, data not shown in the Results). The overall benefit (determined as good outcome at 3 months) of patients who received antihyperthermic treatment was 31.8%.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…This is probably due to the multiple mechanisms that can condition the temperature increase in ICH, and the type of hemorrhage is undoubtedly one of these variables. 13 In our series, the therapeutic response was positive in only 31.1% of hypertensive ICH, in 42.9% of amyloid ICH, in 25.0% associated with antiplatelets/anticoagulants, and in 74.2% of indeterminate cases (p < 0.0001, data not shown in the Results). The overall benefit (determined as good outcome at 3 months) of patients who received antihyperthermic treatment was 31.8%.…”
Section: Discussionmentioning
confidence: 42%
“…[8][9][10] Hyperthermia has been associated with poor outcome in ICH 11 and with the increase of PHHD volume, 12 especially by hypertensive mechanisms. 13 Hypothermia has been proposed as a treatment for ICH that is associated with a decrease in PHHD. However, this kind of treatment is not recommended for patients with ICH due to the high morbidity and mortality, and more clinical trials are needed to verify its efficacy and safety.…”
mentioning
confidence: 99%
“…Binding of SARS-CoV-2 to ACE2 receptors situated on lung and capillary epithelial cells triggers the formation of a cytokine storm characterized by an increased expression of inflammatory cytokines such as IL-1, IL-6, and TNF-α (16,23). Peripheral inflammation can lead to increased BBB permeability and the rupture of blood vessels causing brain edema and ICH (68). Cerebral SARS-CoV-2 infection activates CD4+ immune cells that in turn induce cytokine release from resident microglia and macrophages.…”
Section: Structure and Function Of Sars-cov-2mentioning
confidence: 99%
“…It was with great interest that we read the publication by Iglesias-Rey et al [1], who found an association of elevated body temperature with perihemorrhagic edema (PHE) evolution exclusively in hypertension-related intracerebral hemorrhage (ICH). In accordance with pathophysiologic findings, others found an independent association of PHE evolution with inflammatory parameters including fever in ICH without further etiological differentiation [2,3].…”
mentioning
confidence: 99%